An Alternative Approach to Combine Orbital Prosthesis and Obturator: A Case Report - Soganci, Gokce; Yalug, Suat; Kocacikli, Mustafa (European Journal of Dentistry, 2011)
This report describes a different approach for diminishing the movements of orbital prosthesis during mimic movements and chewing function. Mechanical devices such as magnets are used to enhance the retention in case lack of the implants. However rigid fixation of obturator and orbital prosthesis can result in movements of the orbital prosthesis during mastication. In this case obturator and orbital prosthesis are combined by magnets. However this combination is not rigid because of an active part which provides movement. This active part allows movements in a space constructed in the acrylic base of orbital prosthesis. Thus, the movements that may occur on orbital prosthesis during chewing can be diminished by this simple mechanism. Due to the fact that designing such a mechanism that minimizes the movements of the orbital prosthesis contributes patient’s comfort. (Eur J Dent 2011;5:459-464)
Keywords: Combined prostheses; Magnets; Movement; Obturator; Orbital prosthesis